2019
DOI: 10.1080/16549716.2019.1656451
|View full text |Cite
|
Sign up to set email alerts
|

Active versus passive case finding for tuberculosis in marginalised and vulnerable populations in India: comparison of treatment outcomes

Abstract: Background: Community-based active case finding (ACF) for tuberculosis (TB) implemented among marginalised and vulnerable populations in 285 districts of India resulted in reduction of diagnosis delay and prevalence of catastrophic costs due to TB diagnosis. We were interested to know whether this translated into improved treatment outcomes. Globally, there is limited published literature from marginalised and vulnerable populations on the independent effect of community-based ACF on treatment outcomes when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…A recently published study from Myanmar reported similar treatment outcomes between cases identi ed actively and passively [28]. Similarly, another study in India did not nd any signi cant difference in the TB treatment outcomes of people detected through active case nding as compared to passive case nding among marginalized and vulnerable populations [29]. Previous studies had the limitation of not adjusting for the potential baseline characteristics and also the follow-up characteristics [28].…”
Section: Discussionmentioning
confidence: 92%
“…A recently published study from Myanmar reported similar treatment outcomes between cases identi ed actively and passively [28]. Similarly, another study in India did not nd any signi cant difference in the TB treatment outcomes of people detected through active case nding as compared to passive case nding among marginalized and vulnerable populations [29]. Previous studies had the limitation of not adjusting for the potential baseline characteristics and also the follow-up characteristics [28].…”
Section: Discussionmentioning
confidence: 92%
“…From 27,270 articles, 18 were eligible [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] (Figure 1 and Table 2); seven were not reported in the previous review [20,[29][30][31][32]36,37]. We only identified n=12/23 (52%) of the outcome indicators sought (Table 1); no studies reported on the remainder.…”
Section: Clinical Reviewmentioning
confidence: 99%
“…Seven observational studies reported on risk groups, including prisoners, [29][30][31][32] migrants, [33] miners, [34] and homeless people. [32,35].…”
Section: Risk Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is pertinent to note that before more evidence is generated, patients diagnosed with TB through ACF should be particularly monitored for treatment outcomes when compared from those diagnosed by PCF, as studies in the past had reported variable treatment outcomes. 24 , 25 , 26 …”
Section: Case Finding Strategies: Passive and Activementioning
confidence: 99%